Experimental measurements of velocity through granular-Liquid flows - Sanvitale, N.; Bowman, E.T.; Genevois, R. (Italian journal of engineering geology and environment, 2011)
This paper describes a series of “small scale” laboratory flume tests designed to examine the motion and arrest of concentrated granular-fluid flows, with a view to understanding debris flows. A non intrusive optical approach which relies on the matching of the refractive index and the planar laser-induced fluorescence techniques (PLIF), is adopted to analyse the flow behaviour of a granular medium in a ‘free surface’ condition and in the context of relatively high-speed movement. A PIV (Particle Image Velocimetry) approach, adapted for geotechnical testing, is used to measure the velocity pro les as obtained from laser-illuminated images through the transparent flowing granular material. PIV analyses of experiments carried out using two different mixtures, one characterized by well-graded and one by uniform particle size distribution, are compared in order to understand the effect of the granular composition on the flow dynamics. The experimental results suggest that the particle size distribution has an influence on the mobility of flowing granular material at a given moisture content. Flow of well-graded mixtures show higher velocity, smaller flow thickness and a larger runout extent. The velocity profiles of the two mixtures, measured at the control section of the flume slope, exhibit different behaviour with a lower degree of shearing for that with uniform particle size distribution.